Handbook of nutrition and food - Berdanier, Carolyn D. (CRC Press LLC, 2011)
With a clear and concise format, Handbook of Nutrition and Food presents the quantitative and qualitative data and information needed by nutritionists, dieticians, and health care professionals. It proceeds from human development to body systems and disease to micro/macro nutrients and concludes with nutrition counseling and community nutrition. Sections include interpretive text to help you understand the background and use of the material.